Syntaxin 17 regulates the localization and function of PGAM5 in mitochondrial division and mitophagy. (20th September 2018) - Sugo, Masashi; Kimura, Hana; Arasaki, Kohei; Amemiya, Toshiki; Hirota, Naohiko; Dohmae, Naoshi; Imai, Yuzuru; Inoshita, Tsuyoshi; Shiba‐Fukushima, Kahori; Hattori, Nobutaka; Cheng, Jinglei; Fujimoto, Toyoshi; et al.
Abstract: PGAM5, a mitochondrial protein phosphatase that is genetically and biochemically linked to PINK1, facilitates mitochondrial division by dephosphorylating the mitochondrial fission factor Drp1. At the onset of mitophagy, PGAM5 is cleaved by PARL, a rhomboid protease that degrades PINK1 in healthy cells, and the cleaved form facilitates the engulfment of damaged mitochondria by autophagosomes by dephosphorylating the mitophagy receptor FUNDC1. Here, we show that the function and localization of PGAM5 are regulated by syntaxin 17 (Stx17), a mitochondria‐associated membrane/mitochondria protein implicated in mitochondrial dynamics in fed cells and autophagy in starved cells. In healthy cells, loss of Stx17 causes PGAM5 aggregation within mitochondria and thereby failure of the dephosphorylation of Drp1, leading to mitochondrial elongation. In Parkin‐mediated mitophagy, Stx17 is prerequisite for PGAM5 to interact with FUNDC1. Our results reveal that the Stx17‐PGAM5 axis plays pivotal roles in mitochondrial division and PINK1/Parkin‐mediated mitophagy. Synopsis: Mitochondrial phosphatase PGAM5 has been shown to regulate mitophagy by dephosphorylating the mitophagy receptor FUNDC1. New data show that syntaxin 17 associates with PGAM5 and regulates its localization and Drp1 and FUNDC1 activation during normal and mitophagic division, respectively. Syntaxin 17 binds PGAM5 and regulates its localization and activity. Syntaxin 17 promotes Drp1 activity by facilitating its PGAM5‐mediated dephosphorylation. Syntaxin 17 is required for the association of PGAM5 with the mitophagy receptor FUNDC1 in mitophagy. Syntaxin 17 and PGAM5 maintain mitochondrial architecture in Drosophila . Abstract : Syntaxin 17 supports PGAM5‐mediated dephosphorylation and activation of fission factor Drp1 in healthy cells by regulating PGAM5 localization.